Use of bioengineering (live pole) and scrap tire for mitigation and repairing of slope failures - Kim Huat, Bujang (2008)
Slope instability, also commonly referred to in the plural as slope failures or landslides, is a serious geological hazard common to many countries of the world. This paper describes two techniques,namley the use of vegetation (bioengineering) approach to mitigate slope failures and use of waste material (scrap tires) for slope repairs. Generally vegetation is seen increasingly as s suitable technique for slope reinforcement especially against shallow failures. This techniques offer an effective, economical and environmentally acceptable means of combating the predicted increase of shallow slope instability due to climate change. Woody vegetations or Live pole, improve stability of forested slopes by providing immediate shear strength enhancement and modifying the saturated soil water regime (mechanical and hydrological effects). A laboratory and field based research into the use of tropical woody species of Live Poles in tropical zones under a Ministry of Science, Technology and Innovation Malaysia research grant at University Putra Malaysia (UPM) Faculty of Engineering is described in this paper. The initial research involved screening trials of potential species for ability to propagate vegetative from large live cuttings obtained from branches of small trees and shrubs followed by field trials in selected trial slopes in the UPM campus. The need to design a cost effective slope repairs prompted the study to design an innovative retaining wall system using waste materials such as scrap car tires.Work done on testing for tensile strength of scrap tires where currently there appeared to be no test standard availabe, design and test of suitable attachment to tie the tire together and the design,construction and performance of field trial of the propose scrap tire retaining wall is described in this paper. The test done on local scrap car tires showed that scrap tires could easily carry tensile load of 20 kN. Polyprolene rope of 12 mm in diameter tied in single loop and two knots could provide the required (matching) strength as joint. Scrap tire retaining wall comprising whole tires tied with polyproplene rope stacked on top of each other and backfilled with in situ cohesive fill showed excellent performance, and was probably the most cost effective solution for repairing slope of up to 6m high.